Give a reason for each step in the following argument to prove the statement for any propositions A, B, and C:
([A → (B ∨C)] ∧¬B ∧¬C) → ¬A
- A → (B ∨C)
- ¬B
- ¬C
- ¬B ∧¬C
- ¬(B ∨C)
- ¬A
What is this problem asking exactly? Am I just describing what's happening? Any help is appreciated
You have to "comment" each line in the proof, specifying if it is a premise or it is derived from previous lines; in this case, what lines and by which rule.
1) $[A → (B ∨ C)] \land \lnot B \land \lnot C$ --- premise
2) $A → (B ∨ C)$ --- from 1) by $\land$-elimination
3) $¬B$ --- from 1) by $\land$-elimination
4) $¬C$ --- from 1) by $\land$-elimintion
4) $¬B ∧ ¬C$ --- from 3) and 4) by $\land$-introuction
5) $\ldots$